"Like little Helsinki girls in the backseat of a tram" - Lindeman, Meri (JOHN BENJAMINS PUBLISHING CO, 2025)
This article explores the conceptions and attitudes that non-linguists have towards Finnish spoken by gay men. Combining folk linguistics and feminist theories, the study utilises interview and survey data for content analysis. The study finds that the main characteristics of speech viewed as "gay" - e.g. high pitch, atypical intonation patterns, nasality, non-canonical /s/ quality, use of affective adjectives - align with the speech stereotypes associated with girls and young women. The article suggests that, even though the attitudes explicitly communicated by the participants are mostly neutral, the language features associated with gay men show a strong relation to extra-linguistic gay stereotypes.